Explaining Zakat Payment Awareness: The Roles of Zakat Knowledge, Religiosity and Income - Fatihatus Sahliyah; Ahmad Fatichuddin (JPSDa: Jurnal Perbankan Syariah Darussalam, 2026)
This study aims to analyze and show the influence of knowledge of Zakat, religiosity, and income towards the intention of fish farmers to pay pond Zakat in coastal area, named Mengare island in East Java Indonesia. The study employs primary data gathered from 60 respondents and uses the Ordinary Leased Square (OLS) method for data analysis. The main result shows that knowledge, religiosity, and income has positive and significantly influence the intention to pay pond zakat. Knowledge is the dominant factor influencing the intention of fish farmers in paying Zakat. This study complements the existing theory. The findings suggest that zakat stakeholders must enhance intensify education about zakat literacy so it can be increasing muzakki’s intention in paying Zakat